Interaction between laminate quality, drilling‐induced delamination and mechanical properties in machining of carbon fibre reinforced plastic (CFRP): Zusammenhänge zwischen der Laminatgüte, bohrungsinduzierten Delaminationen und den mechanischen Eigenschaften bei der Zerspanung von kohlenstofffaserverstärktem Kunststoff (CFK). Issue 11 (10th November 2016) - Haeger, A.; Meinhard, D.; Lissek, F.; Kaufeld, M.; Hoffmann, M. J.; Schneider, G.; Knoblauch, V.
Abstract : In the presented study, the effect of the microstructural quality of carbon fibre reinforced plastic laminates on their machinability is investigated. Additionally, the impact of processing induced porosity and the effect of machining caused delamination on the static strength of the carbon fibre reinforced plastic laminates is examined under variable mechanical loading conditions such as bending, shearing, bearing or tension. Therefore, carbon fibre reinforced plastic laminates based on the advanced carbon/epoxy prepreg T800S/M21 manufactured by Hexcel were cured in two different ways leading to obvious differences in the corresponding microstructural quality. Drilled test specimens with a wide range of typical delamination around the hole have been gained from wear studies of carbide tools. The delamination was quantitatively determined by means of optical inspection techniques. Afterwards, the influence of the loading situation as well as the effect of the laminate orientation on the mechanical strength of the laminates was investigated. The microstructural quality of the carbon fibre reinforced plastic laminates was found to have an obvious influence on matrix dominated mechanical properties such as the apparent interlaminar shear strength. Furthermore, it significantly influences the machinability of the laminate – the porous carbon fibre reinforced plastic tends much more to delaminate than the compact one. In general, the influence of both, porosity and delamination, on static strength strongly depends on the mechanical loading situation. No recognisable effect can be detected for fibre dominated properties like tensile strength. However, for example in bending tests carbon fibre reinforced plastic laminates typically fail due to delamination on the compressive side of the specimen. Under such loading situations the described defects significantly reduce the strength. The reduction in flexural strength after machining is more severe if longitudinally oriented fibres are delaminated at the surface. On the other hand, transversal oriented top plies, which do not significantly contribute to the strength of the laminate, are not as critical as the corresponding longitudinal ones. Thus, it can be concluded that the machining caused defect sensitivity of carbon fibre reinforced plastic laminates strongly depends on their lay‐up and the loading situation.